Estudo de catalisadores coprecipitados CuO/InO - Aguirre, Maria del Carmen (1994)
Cu-Zn catalysts were obtained by coprecipitation of Cu, Zn solutions with Na carbonate solution. The resulting oxides from calcination treatment were analysed by chemical analysis X-Ray diffraction, and measurements of total specific area. The catalysts were evaluated in steam reforming methanol reaction, and their performance was compared with a commercial catalyst. The analyses by atomic absortion, BET area and X-ray diffraction ratified good preparation, texture and relative crystallinity of oxides. The analysis by diffuse reflectance spectroscopy indicated, in the catalyst, 30 - 70 % in weight of CuO/ZnO the presence of ion Cu+2 forming a phase with ZnO. This catalyst shows different physicochemical properties and higher catalytic activity than the other coprecipitated and ternary catalyst of comercial composition. The characterization of physical mixture of composition 30 - 70 % in weight of CuO/ZnO verified the differences of interaction Cu-Zn in comparison with those obtained by coprecipitation.